An Ecofeminist Reading of Ann Pancake’s Strange as this Weather Has Been: Women as Guardians of the Earth - Tahereh Jahandar; Alireza Farahbakhsh (Critical Literary Studies)
The present article aims to analyze Ann Pancake’s Strange as this Weather Has Been through the lens of ecofeminist theories. The study explores the connections between women and nature by focusing on three key areas: inherent affinity and dualism, agency and intrinsic values, and conflict with technology. The article addresses how the novel expresses and upholds ecofeminist concepts and how the female characters challenge the male-dominated power structure by participating in the ecofeminist movement through their actions and words as Earth's guardians. Greta Gaard’s ecofeminist ideas form the theoretical foundation of this research. The article highlights how the primary female characters in the novel exhibit a profound bond with their land and work to safeguard it as guardians of the Earth, embodying resilience, empowerment, and an enduring spirit, and manifest self-confidence and a deep connection with nature. Through this affinity, they portray a sense of belonging and identity with nature. It laments that technology, which is manipulated in capitalist and patriarchal ideologies, treats nature merely as a commodity. The narrative also showcases and criticizes the dire environmental and societal consequences of mountaintop removal mining as a harmful technological practice in Appalachia, which, on a macro level, stands for the world.